Perkembangan Konsumsi Rokok Di Jepang Pada Periode Azuchi-Momoyama Hingga Masa Kini: The Development of Cigarette Consumption in Japan from the Azuchi-Momoyama Period to the Present Day - Ryan Amarta Pratama; Saadah Fitri Asih, Nur; Meilani Prasetio, Viana (Jurnal Pendidikan Bahasa Jepang Undiksha, 2025)
This study aims to describe the culture of smoking in Japan and the development of its consumption in Japanese society from the Azuchi-Momoyama period to the present. This research is based on descriptive research with a qualitative research approach. This data collection technique is based on Arikunto's documentation method or literature study where all sources of information and data are obtained from documents, journals, articles, websites, and so on. Then the analysis technique used is qualitative data analysis [1] referred to the theory by Miles. In the study, it can be seen that conventional cigarettes such as cigarettes are preferred in Japan. How to consume cigarettes or tobacco products in Japan is generally smoked in the form of cigarettes, or chewed. Then, the amount of cigarette consumption in Japan is gradually and significantly decreasing from year to year. It can be concluded, observing the development of cigarette consumption in Japan is very interesting and as an additional insight into Japanese history and culture, as well as knowing the conditions and rules that apply to smoking in Japan.